2009
DOI: 10.1182/blood-2009-05-223172
|View full text |Cite
|
Sign up to set email alerts
|

Donor-recipient mismatches in MHC class I chain-related gene A in unrelated donor transplantation lead to increased incidence of acute graft-versus-host disease

Abstract: The polymorphic products of major histocompatibility complex class I-related chain A (MICA) genes are important in solid organ transplantation rejection. MICA expression is limited to gut epithelium and may play a role in triggering acute graft-versus-host disease (aGVHD). A total of 236 recipients of unrelated donor transplantation were studied. Donor-recipient human leukocyte antigen (HLA) match was 10/10 human leukocyte antigen (HLA-A, -B, -C, -DRB1, -DQB1) in 73% and MICA mismatch in 8.4%. Because of physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 25 publications
7
73
0
5
Order By: Relevance
“…21,25 No significant mismatch in this SNP was found to be associated with any clinical outcome in our cohort (supplemental Table 6). Parmar et al 22 reported a higher rate of grade II-IV acute GVHD in MICA-mismatched vs matched patients. These findings were, however, immediately challenged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,25 No significant mismatch in this SNP was found to be associated with any clinical outcome in our cohort (supplemental Table 6). Parmar et al 22 reported a higher rate of grade II-IV acute GVHD in MICA-mismatched vs matched patients. These findings were, however, immediately challenged.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] In 2 independent small cohorts of sibling and unrelated donor HCT, respectively, the recipients (but not the donors) were genotyped for the SNP encoding p.M129V, 38 which was found to be significantly associated with clinical outcome, albeit in opposite trends. 21,25 No significant mismatch in this SNP was found to be associated with any clinical outcome in our cohort (supplemental Table 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Genes in the TNF block, MICA/MICB and microsatellite markers are of specific interest because they are in linkage disequilibrium (LD) with the classical HLA genes and could be inherited together as one genetic unit. [13][14][15][18][19][20][21] The presence of FH in patients also affects the probability and speed of identifying a matched UD. [22][23][24][25][26][27][28] It is essential to know the HLA distribution of each population at an allelic level in order to define whether a patient has a high or low probability of finding a matched donor.…”
Section: Introductionmentioning
confidence: 99%
“…5 The role of some of these non-HLA genes have been studied (reviewed [6][7][8][9][10] ): single nucleotide polymorphisms and/or microsatellites within cytokine (-receptor) genes and other non-HLA encoded genes, including those of the innate immune system, may indeed influence HSCT outcome. [11][12][13][14][15][16][17] Genes in the TNF block, MICA/MICB and microsatellite markers are of specific interest because they are in linkage disequilibrium (LD) with the classical HLA genes and could be inherited together as one genetic unit. [13][14][15][18][19][20][21] The presence of FH in patients also affects the probability and speed of identifying a matched UD.…”
Section: Introductionmentioning
confidence: 99%